The effects of surface modification on aerodynamic characteristics of airfoil DU 06 W 200 at low Reynolds numbers,. (November 2022) - Zargar, Omid Ali; Lin, Tee; Zebua, Andrew Gare; Lai, Ting-Jun; Shih, Yang-Cheng; Hu, Shih-Cheng; Leggett, Graham
Abstract: In this paper the flow characteristics and velocity fields over the vertical axis wind turbines DU 06 W 200 airfoil developed by Delft University of Technology and some other innovative designs are examined by computational fluid dynamics (CFD) simulation and particle image velocimetry (PIV) measurements. In these case studies a modification of the plain airfoil upper and/or lower surfaces was applied with the assistance of different techniques. CFD was conducted using the turbulent model of RANS k- ω SST. The PIV experiments were performed using a wind tunnel test and smoke flow visualization. Different practical cases, namely riblet under surface, riblet above surface, cavity front, cavity back, double cavity, single riblet, and spoiler, were designed and examined. Moreover, two hybrid blade airfoils designed and inspired by combining the DU 06 W 200 and NACA 63215 developed by National Advisory Committee for Aeronautics (NACA) were also tested. The results show that the new design hybrid blade airfoil can significantly modify the flow pattern over the airfoil and improve aerodynamic performance. The new design hybrid blade airfoil could deliver improved efficiency for industrial applications, specifically for the design and development of vertical axis wind turbines.